Bung Hatta, Dari Era Kolonial Hingga Orde Baru: Sebuah Refleksi - Malikul Kusno (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2016)
This article is aimed at rerflecting Hatta poliotical biography. His life span can be devided into three stages. First (1921-1932) when Hatta studied in Netherland; this period gave the greatest experience for Hatta due to his involvement in the worldwide interaction and organizations. Second (1932-1945) after he finished his education and came back to Indo- nesia; He put an emphasis on his political activities to unite the struggle vision and avoid internal fragmentation. Third (1945–1956), this is the most complicated and critical period of Hatta political career. He for many times felt disappointed in politic.